2006
DOI: 10.1623/hysj.51.2.336
|View full text |Cite
|
Sign up to set email alerts
|

Ice cover as an indicator of winter air temperature changes: case study of the Polish Lowland lakes

Abstract: Observations of ice cover and winter air temperature measurements were carried out on six lakes in northern Poland during the period 1961-2000. Detailed analyses of the dates of formation and termination of the ice cover, the duration of maximum thickness and ice-free period during winter were carried out. Various tendencies were found in the time series of the earliest freeze-up dates, whereas the latest ice break-up dates were recorded to occur much earlier than in the past on all the lakes, with time advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
67
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 10 publications
6
67
0
4
Order By: Relevance
“…There have been more and more published articles recently dealing with the ice regime of water bodies and investigating this issue in the long-term (LIVINGSTONE, 1997(LIVINGSTONE, , 1999(LIVINGSTONE, , 2000(LIVINGSTONE, , 2003MAGNUSON ET AL., 2000;MARSZELEWSKI & SKOWRON, 2006;SKOWRON, 2009SKOWRON, , 2011CHOIŃSKI ET AL., 2015). This approach recognizes that they are one of the indicators of climate change taking place nowadays (MAGNUSON ET AL., However, there are hardly any studies where the researchers made daily observations and measurements of the ice phenomena within one or two water regions (RZĘTAŁA & RZĘTAŁA, 2009RZĘTAŁA, 2012RZĘTAŁA, , 2014MACHOWSKI, 2013MACHOWSKI, , 2014.…”
Section: Introductionmentioning
confidence: 99%
“…There have been more and more published articles recently dealing with the ice regime of water bodies and investigating this issue in the long-term (LIVINGSTONE, 1997(LIVINGSTONE, , 1999(LIVINGSTONE, , 2000(LIVINGSTONE, , 2003MAGNUSON ET AL., 2000;MARSZELEWSKI & SKOWRON, 2006;SKOWRON, 2009SKOWRON, , 2011CHOIŃSKI ET AL., 2015). This approach recognizes that they are one of the indicators of climate change taking place nowadays (MAGNUSON ET AL., However, there are hardly any studies where the researchers made daily observations and measurements of the ice phenomena within one or two water regions (RZĘTAŁA & RZĘTAŁA, 2009RZĘTAŁA, 2012RZĘTAŁA, , 2014MACHOWSKI, 2013MACHOWSKI, , 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Maksymiuk et al (2008) detected an increasing, statistically significant trend in winter air temperature and a decreasing trend in snow cover thickness in the Biebrza River basin. Marszelewski and Skowron (2006) analysed various indicators related to lake ice cover and winter air temperature and concluded that the recently observed modifications of the ice cover regime of lakes reflect the increase in winter temperature. Trends and projections in precipitation, another key driver of the hydrological system, are less consistent than for temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature in the winter months December to March (from the region Stockholm-Tallinn-St. Petersburg) was calibrated against breakup date in the port of Tallinn (Gulf of Finland) for a long interval, 1757-1999 (Tarand and Nordli 2001), resulting in a slope of 0.098°C/day. Duration of ice cover in Polish lowland lakes was related to the predictor December-March temperature for the period 1961-2000 (Marszelewski and Skowron 2006), giving jb 1 j slopes between 0.06°C/day and 0.13°C/day (no error bars). Finally, air temperature at around March in Vladivostok versus breakup date in lake Khanka (about 160 km north) for the short time span 1984-2003(Nonaka et al 2007) exhibited a linear calibration with a slope of 0.26°C/day (no error bars).…”
Section: Discussionmentioning
confidence: 99%